16th International Symposium on Sound Engineering and Tonmeistering - Sound Engineering and Tonmeistering, 16th International Symposium (Archives of Acoustics, 2016)
The 16th International Symposium on Sound Engineering and Tonmeistering (ISSET) organized by the Institute of Radioelectronics and Multimedia Technology (Warsaw University of Technology), Department of Sound Engineering (Fryderyk Chopin University of Music) and the Polish Radio, under auspicious of the Polish Section of the Audio Engineering Society was held in Warsaw on October 8-10 in 2015. The main topics of the Symposium covered mostly all domains of audio engineering, i.e. musical acoustics, noise control, signal processing, room acoustics, radio and television, multimedia, sound engineering and tonmeistering, perception and quality assessment, and many others. The extra attention has been paid for the problems of loudness of audio programs in radio and TV broadcasting. Over 60 people from different branches of audio technology participated in this Symposium and shared their knowledge and experiences during the paper sessions, technical tours, workshops and special presentations. The selection of abstracts of the papers presented at the ISSET’2015 are inserted below.